"We're socialists not nationalists": British labour and the national question(s). Issue 2 (17th August 2022) - Brown Swan, Coree
Abstract: The UK Labour Party, which in government delivered devolution to Scotland and Wales, has struggled to adapt to a multilevel and increasingly territorialised political space, where demands for significant territorial reform grow ever louder. These challenges intensified with the Scottish independence referendum and the United Kingdom's exit from the European Union. During this prolonged constitutional moment, the Labour Party has had to articulate the case for a plurinational and multicultural British identity and for the Union, and to a large degree, has struggled to do so. Capturing the period from 2012 to 2020, this article examines the discursive strategies adopted by the Labour Party and individuals within it. It identifies a deep discomfort, more pronounced in London and Edinburgh than in Cardiff, with the national questions and a reliance on largely instrumental arguments, albeit ones rooted in traditional left‐wing values of welfare and social solidarity between working people.